Identification of subgroups by risk of graft failure after paediatric renal transplantation: application of survival tree models on the ESPN/ERA-EDTA Registry - Lofaro, Danilo; Jager, Kitty J.; Abu-Hanna, Ameen; Groothoff, Jaap W.; Arikoski, Pekka; Höcker, Britta; Roussey-Kesler, Gwenaelle; Spasojević, Brankica; Verrina, Enrico; Schaefer, Franz; van Stralen, Karlijn J.; Coppo, R.; et al. (Nephrology, dialysis, transplantation, 2016)
AbstractBackground. Identification of patient groups by risk of renal graft loss might be helpful for accurate patient counselling and clinical decision-making
Members of the ESPN/ERA-EDTA Registry Committee, D. Shitza, R. Kramar, R. Oberbauer, S. Baiko, A. Sukalo, K. van Hoeck, F.Collart, J.M. des Grottes, D. Pokrajac, H. Resić, B. Prnjavorac, D. Roussinov, D. Batinić,M. Lemac, J. Slavicek, T. Seeman, K. Vondrak, J.G. Heaf, U.Toots, P. Finne, C. Grönhagen-Riska, C. Couchoud, M. Lasalle, E. Sahpazova, G. Gersdorf, C. Barth, C. Scholz, B. Tönshoff, G. Ioannidis, A. Kapogiannis, F. Papachristou, G. Reusz, S. Túri, L.Szabó, T. Szabó, G. Reusz, Zs. Györke, E. Kis, R. Palsson, V. Ed-vardsson, F. Mencarelli, F. Paglialonga, C. Pecoraro, S. Picca, R. Roperto, E. Vidal, E. Verrina, A. Jankauskiene, B. Pundziene, V. Said-Conti, S. Gatcan, O. Berbeca, N. Zaikova, S. Pavićević, T. Leivestad, A. Bjerre, A. Zurowska, I. Zagozdzon, C. Mota, M. Almeida, C. Afonso, G. Mircescu, L. Garneata, E. Podgoreanu, E.A. Molchanova, N.A. Tomilina, B.T. Bikbov, M. Kostic, A. Peco-Antic, S. Puric, D. Kruscic, B. Spasojevic-Dimitrijeva, G. Milosecski-Lomic, D. Paripovic, L. Podracka, G. Kolvek, J. Buturovic-Ponikvar, G. Novljan, N. Battelino, A. Alonso Melgar and the Spanish Pediatric Registry, S. Schön, K.G. Prütz, A. Seeberger, L. Backmän, M. Evans, C.E. Kuenhi, E. Maurer, G. Laube, G. Simometi, A. Hoitsma, A. Hemkeandall centres participating in the RichQ study, R. Topaloglu, A.Duzova, D. Ivanov, M. Sinha and the staff of the UK renal registry for contributing data to the ESPN/ERA-EDTA Registry
Published: 27 August 2015
Gesehen am 14.05.2020